Derivative of sawtooth - interpretation of result

7 Ansichten (letzte 30 Tage)
Gennaro Arguzzi
Gennaro Arguzzi am 3 Jul. 2017
Bearbeitet: David Goodmanson am 4 Jul. 2017
Hi everyone. I derived a sawtooth function:
with the following code:
syms t
x=t*(heaviside(t)-heaviside(t-3));
y=diff(x);
The result is: y = heaviside(t) - heaviside(t - 3) - t*(dirac(t - 3) - dirac(t)). I don't understand why the delta Dirac is multiplied per t. I know that x(t)*delta(t-3)=x(0)*delta(t-3), but x(0)=0 thus, for matlab x(0)*delta(t-3)=0.
Thank you very much.

Antworten (1)

David Goodmanson
David Goodmanson am 3 Jul. 2017
Bearbeitet: David Goodmanson am 3 Jul. 2017
Hello Gennaro,
This is just the formula for the derivative of a product,
t * ( heaviside(t) -heaviside(t-3) )
where
d/dt heaviside(t) = delta(t) and d/dt heaviside(t-3) = delta(t-3).
And as a distribution,
Integral x(t)*delta(t-3) dt = x(3)
and (assuming limits of integration include t=3)
Integral x(3)*delta(t-3) dt = x(3) * Integral delta(t-3) dt = x(3)
so effectively
(x(t)-x(3))*delta(t-3) = 0
not
(x(t)-x(0))*delta(t-3) = 0
  2 Kommentare
Gennaro Arguzzi
Gennaro Arguzzi am 3 Jul. 2017
Bearbeitet: Gennaro Arguzzi am 3 Jul. 2017
Hi @David Goodmanson, I don't understand the graphic meaning of t*delta(t-3). When my professor evaluate the derivative, he wrote only the term d(t)/dt*delta(t-3)=1*delta(t-3). The graphic meaning of delta(t-3) is clear, but t*delta(t-3) is unclear for me. PS: I don't know the distributions. Thank you very much.
David Goodmanson
David Goodmanson am 3 Jul. 2017
Bearbeitet: David Goodmanson am 4 Jul. 2017
Hello Gennaro, I will try to give a better version of what is in the answer. The delta "function" delta(t) is a kind of spike that has a nonzero value only at t=0, and the total area under its curve = 1. The translated function delta(t-3) is nonzero only when its argument is zero, so at t=3.
For the product t*delta(t-3), t=3 is the only value that matters and gives something nonzero, so you can substitute and effectively
t*delta(t-3) = 3*delta(t-3)
You can also look at what happens when you integrate across the location of the delta function.
fundamental definition:
Integral g(t)*delta(t-t0) dt = g(t0) for any g(t)
so if g(t) = t,
Integral t*delta(t-3) dt = 3
but
Integral 3*delta(t-3) dt = 3 (delta function has area 1)
so effectively
t*delta(t-3) = 3*delta(t-3)
If your prof wrote that effectively
t*delta(t-3) = delta(t-3)
I would say he or she made a mistake.

Melden Sie sich an, um zu kommentieren.

Kategorien

Mehr zu Creating and Concatenating Matrices finden Sie in Help Center und File Exchange

Tags

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by